The Analysis Study of Clinical Benefits and Risk of Oral Anticoagulant Therapy in Patient with Chronic Kidney Disease : A Comprehensive Systematic Review - Rafi, Muhammad Faiz Haidar; Muhammad, Riza Fadhila (The International Journal of Medical Science and Health Research, 2024)
Background: Arterial hypertension and diabetes mellitus are the primary causes of Chronic kidney disease CKD, while CKD is recognized as an independent risk factor for the onset of CVD. The aim of this study to show about clinical benefits and risk of oral anticoagulant therapy in patient with chronic kidney disease. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Sciencedirect were used to do this. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Although there is a need for cardiorenal consensus regarding anticoagulation in CKD, adequate selection of the anticoagulant type and careful monitoring are some extremely useful indications for overcoming management challenges.